Guideline-based development approach for IoT home applications / Norizan A Kamaludeen - Norizan , A Kamaludeen (2019)
The concept of Smart Home is changing into a practice with more home devices and sensors are interconnected into an individual home infrastructure. The main objective of Smart Home is to make living safer, for security and peace of mind, convenience, comfort and well-being. Presently, developing IoT Home application systems progressively becomes crucial due to trending technologies and economic in the real world. IoT Home application development is different from any software system development as it additionally involves hardware development aspect to it. Most of the software developers do not have experience in hardware development. They are also lack of awareness of the significance of hardware development and its essential information as well as lack of skill in the development process. In this context, software developers and programmers are in the need of competent information with regards to hardware development or some directions in place for them to perform IoT application development. In the meantime, amid IoT development, hardware engineers familiar with IoT hardware may stand up to challenges with mobile or web application development due to inadequate experience or lack of information concerning it. Along these lines, hardware and software engineers clearly require assistance and guidance to work in tandem with IoT application development. Despite the fact that there have been some scattered guidelines important for IoT Home application development in different sources, they do not cover every one of the stages included, both in hardware and software development. Hence, the objective of this study is to propose a guideline-based development approach that provides comprehensive practices and instructions to guide software developers in IoT Home application development process more efficiently. The proposed approach comes in the forms of sequence of steps, checklists, best practices, and patterns. The proposed approach and the IoT Home application developed by employing these guidelines were evaluated by expert and user evaluation. The result of the evaluation shows that the proposed approach is efficient and valid. Meanwhile, the developed IoT Home application has also been evaluated to be effective. Moreover, the proposed guideline-based development approach aims to assist software developers throughout the development process starting from the requirements review process till the mobile application development process.